CONTRADICTIONS OF THE SOCIAL IMAGINARY: MAKING SENSE OF DIGITAL FOOD SNAPS - Larsen, Jessica Nicole (AoIR Selected Papers of Internet Research, 2015)
Beyond our biological needs for food, food cultures are arranged from series of complicated and often contradictory magical thinkings, where ideologies of food do not match practices (Kaufman, 2010). The introduction of mobile-social photography into everyday food space has disrupted patterns of thinking about the boundaries between technology and food space, provoking reconsideration of the cognitive and sensory orientation of the individual toward a meal, as well as the social appropriateness of the translation of a meal from a private to a public event. This theoretical discussion is aimed at making sense of these reconsiderations, and addressing the relationship between mobile-social photography and what it means for the contemporary eater to engage with food. Taking and sharing online photos of everyday activities can seem trivial and not ideologically valued. Food photography has been claimed to affect restaurant experience, create conflict between chefs and consumers, and has been ridiculed for its amateurism. On the other hand, like many online social practices, digital food photography may be a method of self-representation and have important social value. Ultimately, however, the ideological criticism of food photography contradicts with its existence as a popular practice among the social collective. This argument conceives the practice of sharing food photos online using the concepts of mediation and remediation to reflect this contradiction in our imagination of the digital foodscape. The digital photo shared online represents the practice of photography and the values inherent in forming identities and sharing ourselves in the constellation of online social spaces (Larsen & Sandbye (2014) coin this as a ‘digital snap’). This discussion conceives digital food snaps as both a remix of the values embedded in photography and online sharing as well as the values of sharing and connecting through food offline remixed in digital space. The resulting claim is that digital food snaps are a transforming the cultural meaning of and reshaping the values of our engagement with food.